Integrating Maqashid Shari’a on Cultural Responsiveneness to Constructing Academic Culture - Syahrur Ramli; Gusrina Fadhila; Ramza Husmen; Aidil Darmawan (Social Journal of Studies in Education, 2026)
This study aims to develop a culturally responsive instrument based on the principles of Maqashid Syariah to address the cultural identity crisis among students at the State Islamic University of Indonesia. Focusing on the integration of five essential safeguards (faith, life, reason, progeny, and wealth) with a hierarchical culturally responsive model, this study specifically examines how the levels of needs, requirements, and embellishments (tahsiniyyah) can map the inclusive attitudes of students. Using the Systematic Literature Review (SLR) methodology, this study synthesizes existing literature to build a comprehensive framework. The results of the study indicate successful integration, where Maqashid Syariah provides a strong ethical and transcendental foundation for measuring cultural responsiveness, going beyond mere social skills to embody the practice of universal Islamic values such as compassion and modesty. This instrument offers a nuanced and spiritually grounded alternative to conventional secular scales, allowing for a more holistic evaluation of how students navigate cultural plurality while remaining rooted in their religious and local wisdom.